Grave Matters - Shushan, E. R. (Ballantine Books New York, 1990)
A curious collection of 500 actual epitaphs, from which we learn of grieving spouses, fatal gluttony, vengeful relations, and all manner of partin commentary
Keywords: Epitaphs